2020
DOI: 10.3390/insects11110800
|View full text |Cite
|
Sign up to set email alerts
|

Foraging Bumblebees Selectively Attend to Other Types of Bees Based on Their Reward-Predictive Value

Abstract: Using social information can be an efficient strategy for learning in a new environment while reducing the risks associated with trial-and-error learning. Whereas social information from conspecifics has long been assumed to be preferentially attended by animals, heterospecifics can also provide relevant information. Because different species may vary in their informative value, using heterospecific social information indiscriminately can be ineffective and even detrimental. Here, we evaluated how selective us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(26 citation statements)
references
References 68 publications
3
23
0
Order By: Relevance
“…Existing literature (Forsman et al 2014;Loukola et al 2020b;Romero-González et al 2020a) provides examples of how SIIU could lead to similar trait divergence as predicted by our simulation model. To acquire social information, individuals need to coexist, which also increases the probability of competition.…”
Section: Trait Divergencesupporting
confidence: 54%
See 4 more Smart Citations
“…Existing literature (Forsman et al 2014;Loukola et al 2020b;Romero-González et al 2020a) provides examples of how SIIU could lead to similar trait divergence as predicted by our simulation model. To acquire social information, individuals need to coexist, which also increases the probability of competition.…”
Section: Trait Divergencesupporting
confidence: 54%
“…Selective interspecific information use (SIIU) has gained increased attention and has been observed in birds Seppänen et al 2011;Loukola et al 2013;Szymkowiak et al 2016;Thorogood et al 2018;Tolvanen et al 2018;Morinay et al 2020;Hämäläinen et al 2021a) and insects (Loukola et al 2020b). This interspecific "reject-theunsuccessful" strategy (Forsman et al 2018;Loukola et al 2020b;Romero-González et al 2020a; but see Slagsvold & Wiebe 2017) complements existing literature on selective social information use including "copy-the-successful" strategy (Laland 2004). In this study, we focus on copying and rejecting an observed behaviour due to their relevance in ecological and evolutionary consequences of SIIU.…”
Section: Main Text 1 Introductionmentioning
confidence: 85%
See 3 more Smart Citations